2015
DOI: 10.2135/cropsci2014.07.0478
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Differentiation of Gender in Buffalograss

Abstract: Buffalograss [Buchloë dactyloides (Nutt.) Engelm. syn. Bouteloua dactyloides (Nutt.) Columbus] is a warm‐season, stoloniferous, perennial grass species native to the Great Plains of North America. Buffalograss is a dioecious species where structural differences can be observed between inflorescences of male and female plants. The genetic mechanisms conferring gender expression in buffalograss are not known. In the present study, RNA‐seq was performed to evaluate the transcriptome of 10 buffalograss female and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…As part of that project, 121,288 total contigs were assembled and 325 differentially expressed transcripts were identified between Prestige and 378. Donze et al (2015) sequenced the transcriptomes of 10 male and 10 female buffalograss F1 progeny from a genetic linkage mapping population to identify transcripts important for gender expression in buffalograss. Donze et al (2015) found 1,734 differentially expressed transcripts (false discovery rate, FDR < 0.01) by gender.…”
Section: Core Ideasmentioning
confidence: 99%
See 3 more Smart Citations
“…As part of that project, 121,288 total contigs were assembled and 325 differentially expressed transcripts were identified between Prestige and 378. Donze et al (2015) sequenced the transcriptomes of 10 male and 10 female buffalograss F1 progeny from a genetic linkage mapping population to identify transcripts important for gender expression in buffalograss. Donze et al (2015) found 1,734 differentially expressed transcripts (false discovery rate, FDR < 0.01) by gender.…”
Section: Core Ideasmentioning
confidence: 99%
“…Donze et al (2015) sequenced the transcriptomes of 10 male and 10 female buffalograss F1 progeny from a genetic linkage mapping population to identify transcripts important for gender expression in buffalograss. Donze et al (2015) found 1,734 differentially expressed transcripts (false discovery rate, FDR < 0.01) by gender. Of those resulting transcripts, 445 had higher expression in male plants, and two were uniquely expressed in the males.…”
Section: Core Ideasmentioning
confidence: 99%
See 2 more Smart Citations